2013
DOI: 10.1073/pnas.1314311110
|View full text |Cite
|
Sign up to set email alerts
|

A universal strategy for visually guided landing

Abstract: Landing is a challenging aspect of flight because, to land safely, speed must be decreased to a value close to zero at touchdown. The mechanisms by which animals achieve this remain unclear. When landing on horizontal surfaces, honey bees control their speed by holding constant the rate of front-to-back image motion (optic flow) generated by the surface as they reduce altitude. As inclination increases, however, this simple pattern of optic flow becomes increasingly complex. How do honey bees control speed whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
157
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(177 citation statements)
references
References 19 publications
(13 reference statements)
10
157
4
Order By: Relevance
“…To safely fly in cluttered environments, insects instead rely on image motion, also known as optic flow 38,39 , generated by their own displacement relative to the surroundings 40 . It has been experimentally shown that their neural system reacts to optic flow patterns 41,42 to produce a large variety of flight capabilities, such as obstacle avoidance 40,43 , speed maintenance 44 , odometry estimation 45 , wall following and corridor centring 46 , altitude regulation 47,48 , orientation control 49 and landing 50,51 . Optic flow intensity is proportional to the distance from objects only during translational movements, but not during rotational movements when it is proportional to the rotational velocity of the agent.…”
Section: Review Insightmentioning
confidence: 99%
“…To safely fly in cluttered environments, insects instead rely on image motion, also known as optic flow 38,39 , generated by their own displacement relative to the surroundings 40 . It has been experimentally shown that their neural system reacts to optic flow patterns 41,42 to produce a large variety of flight capabilities, such as obstacle avoidance 40,43 , speed maintenance 44 , odometry estimation 45 , wall following and corridor centring 46 , altitude regulation 47,48 , orientation control 49 and landing 50,51 . Optic flow intensity is proportional to the distance from objects only during translational movements, but not during rotational movements when it is proportional to the rotational velocity of the agent.…”
Section: Review Insightmentioning
confidence: 99%
“…Exploiting the principles of claws, van der Waals forces and wet adhesion, animals have evolved to generate the required attachment forces (figure 2) [60][61][62][63][64][65][66][67][68]. This enables animals to negotiate and exploit complex surfaces with a combination of effective aerial approaches, contact strategies, surface locomotion techniques and take-off manoeuvres of which the dynamics are not well understood [1,[69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85]. By contrast, aerial robots are just starting to implement some of these successful perching and locomotion strategies.…”
Section: Diversity Of Natural and Engineered Surfacesmentioning
confidence: 99%
“…All of these animals depend on their eyes for situational awareness and navigation [69,70,[82][83][84]97], which is enhanced by echolocation in many bats and some cave dwelling birds [98,99]. The majority of the flying animals rely thus on vision to land on a surface, and their visual feedback allows them to slow before perching.…”
Section: Air-surface Transitions In Flying Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in honey bees (Apis mellifera) and fruit flies (Drosophila melanogaster) have demonstrated that the visual system plays an important role in controlling approach speed to landing surfaces (Evangelista et al, 2010;Srinivasan et al, 2000), as well as triggering key landing behaviors (van Breugel and Dickinson, 2012). In particular, recent work has shown that insects regulate flight speed during landing by the relatively simple strategy of maintaining a constant rate of image expansion (Baird et al, 2013), causing flight speed to decrease smoothly to zero as the landing target draws closer.…”
Section: Introductionmentioning
confidence: 99%